Unpacking the Goal Congruence–Organizational Deviance Relationship: The Roles of Work Engagement and Emotional Intelligence - De Clercq, Dirk; Bouckenooghe, Dave; Raja, Usman; Matsyborska, Ganna (2014)
Drawing from research on person–organization fit, work engagement, and emotional intelligence, this study investigates the mediating role of work engagement in the link between goal congruence and organizational deviance, as well as how this mediating effect might be moderated by emotional intelligence. Data captured from 272 employees of four IT companies show that the goal congruence between employees and their supervisor negatively affects the former’s organizational deviance, though this effect disappears when controlling for the intermediate role of work engagement. Further, emotional intelligence moderates both the positive relationship between goal congruence and work engagement and the negative relationship between work engagement and organizational deviance, such that these relationships become invigorated at higher levels of emotional intelligence. The findings also reveal that the indirect effect of goal congruence on organizational deviance through work engagement is more pronounced at higher levels of emotional intelligence, which offers evidence of moderated mediation. These findings have significant implications for research and practice.
Keywords: Moderated mediation; Emotional intelligence; Work engagement; Goal congruence; Organizational Deviance